Physicians' attitudes to disability pension - impact of diagnosis: an experimental study - Ashley McAllister; Allison Milner; Monika Engblom; Patrick Corrigan; Bo Burström (BMC, 2021)
Abstract Background The purpose of this study is to increase understanding of physicians' attitudes towards disability pension applicants, and the impact of diagnosis. We hypothesize that physicians are more likely to think that patients with physical illnesses should get a disability pension than those with mental illness or alcohol dependence. Disability pension is an important source of income for those unable to work because of a disability and type of diagnosis should not impact accessing these benefits. Methods We conducted an experiment with a 2 by 3 factorial structure in Sweden. Each physician was randomly assigned one of six patient vignettes, with the same background description but with a different diagnosis. Each vignette had a diagnosis of either depression, alcohol dependence or low back pain, and was about a man or a woman. Logistic regression was used to examine the odds of a physician reporting that a patient should get a disability pension. Effects are reported in terms of odds ratios (ORs). Results 1414 Swedish registered physicians in psychiatry or general practice (24% response rate) completed the survey. Physicians assigned the alcohol dependent vignette had OR 0.45 (95% CI: 0.34 to 0.60) for perceiving that a patient should get a disability pension compared to physicians assigned the low back pain vignette. Physicians assigned the depression vignette had OR 1.89 (95% CI: 1.42 to 2.50) for perceiving that a patient should get a disability pension compared to physicians assigned the low back pain vignette. Conclusion The patient diagnosis was associated with the physicians' response regarding if the patient should get a disability pension. A physician's perception is likely to impact a patient's access to disability pension.